Impact of the interval between neoadjuvant immunochemotherapy and surgery on surgical–pathological outcomes in non-small cell lung cancer - Chen, Jiawei; Deng, Hongsheng; He, Jiaxi; Wang, Zhufeng; Li, Shuben (Frontiers in Oncology, 2022)
Introduction The interval between neoadjuvant immunochemotherapy and surgery in patients with non-small cell lung cancer (NSCLC) has not been well characterized. This study investigated the association between the time-to-surgery (TTS) interval and surgical–pathological outcomes. Method Clinical data of patients who received neoadjuvant immun-ochemotherapy followed by surgery for NSCLC between January 2019 and September 2021 were collected. The patients were divided into three groups based on TTS interval: the early-surgery group (ESG), the standard-surgery group (SSG), and the delayed-surgery group (DSG). The primary outcomes were objective response rate (ORR), major pathological response (MPR), and pathological complete response (pCR). The secondary endpoint was surgical outcome. Results Of the 171 patients, 16 (9.4%) received surgery in ≤28 days, 49 (28.7%) received surgery within 29–42 days, and 106 (61.9%) received surgery in ≥43 days after neoadjuvant immunochemotherapy, with a median TTS of 46 days. The postoperative drainage of the ESG group (455.1 ml) was significantly less than that of the SSG group (680.7 ml) and the DSG group (846.5 ml; p = 0.037). However, the TTS interval did not influence the duration of the operation (P = 0.54), the extent of intraoperative bleeding (P = 0.60), or the length of postoperative hospital stay (P = 0.17). The ORR was observed in 69%, 51%, and 56% of patients in the ESG, the SSG, and the DSG, respectively (P = 0.46), and MPR occurred in 50%, 47%, and 58% (P = 0.38) of patients in the ESG, the SSG, and the DSG, respectively. Similarly, no statistically significant difference was found for pCR (ESG: 31%; SSG: 27%; DSG: 42%; P = 0.14). Conclusion This retrospective study indicated that TTS exerts no significant effect on the feasibility and safety of surgery in the neoadjuvant immunochemotherapy setting of NSCLC. Analysis of the TTS interval revealed a tendency for delayed surgery to be associated with a pathological response in NSCLC, although this association was not statistically significant.